Evaluation of Airborne Particulate Matter and Volatile Organic Compounds Released by Three Types of Mosquito Repellents - Soyeon Lee; Jongmin Park; Myoungho Lee; Minjung Kim; Boowook Kim; Kiyoung Lee; Kyungduk Zoh; Chungsik Yoon (Aerosol and Air Quality Research)
Abstract This study investigates the emissions from various mosquito repellents, focusing on particulate matter (PM) and volatile organic compounds (VOCs). PM was measured with a scanning mobility particle sizer (SMPS) and optical particle spectrometer (OPS) in an exposure chamber; VOCs were collected with Tenax TA and analyzed by gas chromatography-mass spectrometry. SMPS measurements in the range of 10–420 nm showed that the coil-types had the highest concentration (13,048 particles cm‒3), followed by the mat-types (119 particles cm‒3), and liquid-types (42 particles cm‒3). However, the percentage of nanoparticles was highest in the liquid-type (50%), followed by the mat (46%) and coil-types (33%) (p < 0.05). According to the OPS measurements, covering a range of 0.3–10 µm, showed the highest value for the coil-types (4,096 particles cm‒3), with similar values for the mat and liquid-types (13 particles cm‒3 each). The percentage of particles < 2.5 µm in size, which can easily enter the lower respiratory tract, was 82–99%. Coil types burn at a much faster rate (29.31 mg min‒1) than liquid (1.89 mg min‒1) and mat types (1.30 mg min‒1), indicating a more intense combustion process. Coil types also lead in emission rates (1.94 × 1010 particles min–1 for 10–420 nm) releasing more particles per minute, followed by liquid (1.87 × 108 particles min‒1) and then mat types (6.34 × 107 particles min‒1), suggesting higher particulate emissions during use. When normalized by usage weight, Coil types again show the highest emission factors (6.59 × 1011 particles g‒1), implying they emit more particles per gram of product burned than liquid (1.82 × 1011 particles g‒1) and mat (4.81 × 1010 particles g‒1) types. The study highlights the need for comprehensive understanding of repellent emissions due to their potential health impacts.